Pengelolaan Keuangan yang Efektif dan Efisien dalam Meningkatkan Kekuatan Ekonomi bagi Masyarakat Papua dan Papua Barat di Indonesia - Agustinus, John (Jurnal Aplikasi Manajemen, 2014)
Effective financial management is to run all of the financial system in accordance with an agreement in which the programming in the financial management of the regional government of Papua and West Papua provinces of deliberation constructed by utilizing a regional development plan for federal funds through the General Allocation Fund and the Special Autonomy Fund . By building use of financial governance with efficient local government found that by using existing funds shall be in accordance with the level of achievement of the program, so that in implementing all programs properly and use appropriate financial management also it will achieve an effective and efficient financial. Research Methods Using a phenomenological study by Weber perspective, researchers examined by interviews with key informants procedures such as Head of Finance of Papua and West Papua. In addition to in-depth interviews are also conducted focus group discussion with financial experts as lecturers and NGOs. Findings: It was found that obtained meaning that the local government financial management are in accordance with the legislation and in the implementation of the program is also in accordance with the plan will be obtained meaning that financial management is the effective and efficient achievement of results in accordance with the program and utilize the funds to the maximum.